Effect of different types of coagulation medium on asymmetric polysulfone membrane for CO2/CH4 gas separation - Nurhana, Shafiee (2010)
The purposed of this study is to determine the best coagulant medium for asymmetric poysulfone membrane. This study was focused on the effect of coagulation medium on asymmetric polysulfone membrane structure and gas separation performance. Flat sheet asymmetric membrane were formed by using three component of dope solution containing 20% polysulfone(PSU), 77% N-Methyl-2-pyrrolidone (NMP), and 3% water. The asymmetric membrane was prepared by a simple dry and wet inversion technique using a developed casting system. Experiment investigation conducted focusing on different coagulant medium, thus representing three different conditions which were immersed in water, methanol and water/methanol (50:50). Permeability of the membrane was examined by using the gas permeability unit available in the Gas Lab. Three membrane samples have been produce with different coagulant medium which were membrane A (immersed in water), membrane B (immersed in methanol), and membrane C (mixture of water and methanol with the percentage 50% water and 50% methanol. These results were then correlated to the gas separation performance in two different pure gases which were Methane (CH4) and Carbon Dioxide (CO2). As a result, fourier transform infrared spectroscopy (FTIR) was used to examine the amount of component in the membrane Morphology of membranes were determined by employing a scanning electron microscopic (SEM) technique. From the result, it can be obtained that water is much better compared to methanol and mixture of water and methanol as a coagulation medium. The selectivity of water also high compared to other. In this study, can be conclude that water react as a good coagulation medium in order to form the morphology of the polysulfone asymmetric membrane.